The Diversity, Specialization of High-tech Industrial Structure And Economic Growth in China - Zhang, Xianhui; Pikas, Bohdan; Lee, Tenpao; Liu, Peigang (Journal of Strategic Innovation and Sustainability, 2017)
This paper measures diversity and specialization of China’s high-tech industrial structure using Herfindahl-Hirschman Index, Shannon-Wiener Index and Kullback-Leibler Divergence. It will analyze the linear and non-linear relationships between them and economic growth. It will also examine the impacts of the high-tech service sector, manufacturing sector, and the scale of high-tech enterprises on growth. It has been found that there is a U-shaped non-linear relationship between the internal structure of high-tech industry and growth, based on provincial panel data. Secondly, the differentiation of hightech industrial structure on the national-level and regional-level significantly promotes growth; therefore different optimal structures should be formed among all provinces. Thirdly, the high-tech service sector which is conductive to growth should be encouraged to develop. Lastly, to some extent, large and medium-sized high-tech enterprises have negative impacts on growth, and the development of medium and small-sized high-tech enterprises should be supported.